Rapid prototyping and patient-specific pre-contoured reconstruction plate for comminuted fractures of the mandible. Issue 10 (December 2015) - Fowell, C.; Edmondson, S.; Martin, T.; Praveen, P.
Abstract: The clinical use of rapid prototype, 3-dimensional models and pre-bent reconstruction plates is recognised for mandibular reconstruction after resection of cancer. We describe a new approach using similar techniques in the management of complicated mandibular fractures.